2021
DOI: 10.2991/assehr.k.210909.096
|View full text |Cite
|
Sign up to set email alerts
|

A Flood Water Level and Risk Analysis in Langsa River Aceh Province

Abstract: Langsa river that crosses the city during high rainfall often experiences flooding around the river's border. This is due to the river which is not being able to accommodate the excess discharge so that the overflow of water has a negative impact on the facilities and infrastructure around the river. In addition, flooding is also affected by the damage of Langsa watersheds which is characterized by a decrease in the ability of storing the water. There are few information available regarding the high potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Analysis of the frequency distribution by dividing rainfall using the Thiessen polygon method as was done in research [9] and analyzing the distribution of return period rainfall using the normal distribution, normal log, Pearson III log, and Gumbel methods. Furthermore, an analysis of rainfall-runoff was conducted using the Synthetic Unit Hydrograph (SUH) technique to generate flood discharge hydrographs with a 2-year return period [32].…”
Section: Figure 4 Flow Chart Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the frequency distribution by dividing rainfall using the Thiessen polygon method as was done in research [9] and analyzing the distribution of return period rainfall using the normal distribution, normal log, Pearson III log, and Gumbel methods. Furthermore, an analysis of rainfall-runoff was conducted using the Synthetic Unit Hydrograph (SUH) technique to generate flood discharge hydrographs with a 2-year return period [32].…”
Section: Figure 4 Flow Chart Of Studymentioning
confidence: 99%
“…Based on the recorded flood event, several previous studies have indicated an increasing flood event in both flood-vulnerable areas, the downstream and upper part of Langsa River, due to the land use change and urbanization [8][9][10]. The flood problem in the downstream part of Langsa River is comparable to the flood problem in the downstream part of Ciliwung River Jakarta City [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%